2020
DOI: 10.1007/s11368-020-02677-1
|View full text |Cite
|
Sign up to set email alerts
|

Chromium(VI) reduction and accumulation on the kaolinite surface in the presence of cationic soil flocculant

Abstract: Purpose Heavy metal soluble forms pose a threat to plants, soil microflora, and microfauna. To limit their toxicity and mobility, various immobilizing additives are being developed. The main aim of the study was to determine the influence of soil flocculant (cationic polyacrylamide (CtPAM)) on the hexavalent chromium ion reduction and accumulation on the kaolinite surface. In this way, the efficiency of the selected polymer conditioner in the soil remediation was determined. Materials and methods The adsorbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…The valence forces through the exchange or sharing of electrons between adsorbate and adsorbent. Such a good fitting of experimental data to PSO was also observed during the study on lead(II), chromium(VI) and copper(II) adsorption on kaolinite [ 41 , 42 , 43 ], as well as copper(II) and silver(I) ions on biochar [ 44 , 45 ]. However, it must be emphasized that some researchers do not agree with these assumptions.…”
Section: Resultssupporting
confidence: 65%
“…The valence forces through the exchange or sharing of electrons between adsorbate and adsorbent. Such a good fitting of experimental data to PSO was also observed during the study on lead(II), chromium(VI) and copper(II) adsorption on kaolinite [ 41 , 42 , 43 ], as well as copper(II) and silver(I) ions on biochar [ 44 , 45 ]. However, it must be emphasized that some researchers do not agree with these assumptions.…”
Section: Resultssupporting
confidence: 65%
“…In addition to electrostatic interactions, Cu(II) adsorption on kaolinite may be connected by other mechanisms, i.e., ion exchange, surface complexation and van der Waals attractions [ 31 ]. The previous study on the adsorption of lead(II) and chromium(VI) ions on kaolinite also indicated the best fitting of adsorption isotherm data to Langmuir model [ 11 , 12 , 32 ].…”
Section: Resultsmentioning
confidence: 94%
“…Its specific surface area equals 8.02 m 2 /g, while total pore volume (V p ) is 0.0287 cm 3 /g. It contains two groups of mesopores of average diameters equal to 3.8 and 11.7 nm [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other ionic substances may also affect the adsorption of metal ions (Wiśniewska et al 2018;Szewczuk-Karpisz et al 2020;Fijałkowska et al 2020).…”
Section: Introductionmentioning
confidence: 99%